جدلية العدالة والمساواة في النظرية السياسية المعاصرة: دراسة في نظرية العدالة لجون راولز - عباسي, كريمة (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
أصبحت مسألة العدالة والمساواة هاجس الفكر السياسي والأخلاقي المعاصر على اختلاف مرجعياته ومدارسه، ومع تنامي الاهتمام بقضايا العدالة، برزت إشكالية تحقيق العدالة من خلال جدلية العدل والمساواة، ويعد جون رولز من أبرز فلاسفة الفكر الغربى السياسى المعاصر ، حيث استطاع تطوير نظرية قائمة على مبادئ تؤسس لتحقيق العدالة وذلك من خلال اعتماد مبدأ مهم وهو المساواة بين الأفراد. The issue of justice and equality has become an obsession for contemporary political and ethical thought, with its various references and schools, and with the growing interest in justice issues, The problem of achieving justice has emerged through the debate on justice and equality, and John Rawls is one of the most prominent philosophers of contemporary Western political thought, Where he was able to develop a theory based on principles establishing the achievement of justice by adopting an important principle, which is equality between individuals, His approach to justice was the most important in contemporary political theory